PENGARUH LINGKUNGAN SOSIAL TERHADAP BUDAYA LITERASI SISWA DI MADRASAH ALIYAH AL-HIKMAH BANDAR LAMPUNG - Eliza Fadila Syafitri; Yetri Yetri; Eni Amaliah; Riyuzen Praja Tuala (STKIP Pesisir Selatan, 2026)
One factor that can influence the development of a student's literacy culture is their social environment. The social environment is a system of interactions between individuals and various parties around them that can influence their attitudes, behaviors, and habits in everyday life. This study aims to analyze the influence of the social environment on students’ literacy culture and its contribution to literacy culture at Madrasah Aliyah Al-Hikmah Bandar Lampung. The research employs a quantitative correlational approach. The population consisted of 323 students, with a sample of 179 students selected using cluster sampling. Data were collected through Likert-scale questionnaires, and simple linear regression was used for data analysis. The results indicate that the t-value is 12.171, which is greater than the t-table value of 1.973, leading to the rejection of H₀ and acceptance of Hₐ. This finding confirms that the social environment significantly affects students’ literacy culture. Furthermore, the coefficient of determination (R²) is 0.456, suggesting that the social environment contributes 45.6% to students’ literacy culture, while the remaining 54.4% is influenced by other factors not examined in this study.